Post-activation performance enhancement does not occur following a large hand-paddles and parachute-resisted warm-up routine in collegiate swimmers - Bufalo, Santiago Soares; Fontanetti, Gabriel; Barreto, Renan Vieira; Benazzi, Gabriel Rocha; Junior, Rubens Correa; Marangoni, Victor; Bassan, Natália de Menezes; Denadai, Benedito Sérgio; Greco, Camila Coelho; Vilas-Boas, João Paulo; Lima, Leonardo Coelho Rabello de (Frontiers in Sports and Active Living, 2023)
Our aim was to investigate if using a warm-up routine that included parachute-resisted sprints with large hand-paddles improves 50-m freestyle performance in trained collegiate swimmers. Twelve swimmers (23.9±2.2 years, 179±7 cm, 77.1±10.6 kg) participated in the study and completed two 50m freestyle races, each preceded by a different warm-up routine, either control (CON) or experimental (EXP). The warm-up routines consisted of 500 m of swimming at self-selected speed, followed by four 10-second sprints with 1-minute rest intervals. During EXP, sprints were performed using large hand-paddles and a swimming parachute, while during CON, sprints were performed freely. Performance and technique were assessed during the 50-m freestyle races. We found no significant differences in 25-and 50-m performance times (CON: 12.6±0.8 vs EXP: 12.5±0.8 s, ES = 0.125; and CON: 26.8±1.6 vs EXP: 26.7±1.7 s, ES = 0.06, respectively) between the two conditions.Mean stroke length (CON: 2.04±0.21 vs EXP: 2.02±0.22 m•cycle -1 , ES = 0.09), stroke frequency (CON: 55.4±5.3 vs EXP: 56.3±5.2 cycles•s -1 , ES = 0.17), and propulsive time (CON: 0.62±0.07 vs EXP: 0.61±0.06 s, ES = 0.15) were also not different between conditions. It is possible that the CON warm-up routine induced the priming effects that lead to PAPE, or that the EXP warm-up routine This is a provisional file, not the final typeset article primed the athletes further but also induced greater fatigue, resulting in no significant effects on swimming performance. Our findings suggest that parachute-resisted sprints with hand-paddles during warm-up do not enhance 50-m freestyle swimming performance in trained collegiate swimmers. Coaches and practitioners should consider exploring different warm-up protocols to identify what works best for their athletes.